Anatomical and clinical aspects of the posterior interosseous nerve of the forearm - Lepich, Tomasz; Karaś, Radosław; Kania, Kamil; Machnik-Broncel, Joanna; Barszczewski, Konrad; Szewczyk, Wojciech; Bajor, Grzegorz (Medical Studies/Studia Medyczne, 2024)
The radial nerve arises from the brachial plexus posterior cord from roots C5-Th1. It divides into two terminal branches: superficial and deep. The superficial branch is mostly sensory. From the deep branch arises the posterior interosseous nerve of the forearm. The deep branch of the radial nerve passes through the arcade of Frohse. The arcade of Frohse begins in the apex of the lateral epicondyle of the humerus and is attached to its medial part. It is the highest, proximal part of the supinator muscle, which may have a tendinous or membranous structure. Significant topographic points that are useful in describing the posterior interosseous nerve of the forearm are the radial channel and arcade of Frohse. There exists the anatomical variation of the distal part of the posterior interosseous nerve of the forearm. It is called the Froment-Rauber nerve. Posterior interosseous nerve of forearm dysfunction leads to radial nerve syndrome. There are two different syndromes which are associated with posterior interosseous nerve of forearm dysfunction: radial tunnel syndrome and posterior interosseous nerve syndrome. These syndromes are distinguished on the basis of characteristic symptoms.